Designing a professional development model for technical teachers in order to teach entrepreneurship in technical schools - hosein hasankhani; Niloufar Mortazanejad; maryam sameri (مدیریت و چشم انداز آموزش)
The purpose of the current research is to design a professional development model for technical and professional art students in order to teach entrepreneurship in conservatories. The research method is developmental according to its purpose, and qualitative in terms of implementation. The statistical population includes 24 experts and informants, selected by purposeful and snowball sampling. The studied community includes 1) theoretical foundations of formal and public education in the Islamic Republic of Iran; 2) National curriculum; 3) the objectives of the secondary education course; and 4) the description of the duties of the technical and professional course students. Data collection tools include semi-structured interviews. Data analysis using qualitative content analysis method is of inductive type. To validate the findings, the four criteria of "reliability", "credibility", "verifiability" and "transferability" of qualitative studies have been used. In the analysis of the findings, 191 "open codes" were identified, and by classifying them, the components of the model include the philosophy and why of professional development, approach and direction, principles, goals, levels, the role of art students, qualifications, processes, obstacles, and consequences were identified as the main elements of the model. The results of the current research can be used by the Ministry of Education and Culture in policies related to the empowerment of art students in order to promote entrepreneurship education in conservatories; and recommendations and guidelines provided in the template can be used at the levels of general administrations, management of educational districts and schools. Extended abstract Introduction In fact, human development is the concept of development, expansion of human beings, empowerment of the scope of opportunities, and benefiting from freedom; which leads to the preservation of human ideals and values. The improvement of the human development index represents the empowerment of people to achieve the goal of improving their living standards, which is achieved through the use of human capabilities (Montazeri & Renani, 2022). In this regard, the educational system as a sensitive and important social system has a special position and it will be able to perform its important task efficiently provided that it has the right human resources and has a healthy and dynamic organization (Tayarzadeh et al., 2021). In this regard, education and training, as the largest organization in charge of the human resources of the country's labor market plays a vital role in reducing the country's unemployment rate, with features such as wide and appropriate educational coverage, having the forthcoming generation at the right age to learn principles and concepts, and train human resources before entering the labor market. In fact, by providing the necessary training at the right time, in addition to transferring information and concepts of entrepreneurship to students, education provides the basis for the growth of many characteristics and necessary skills of entrepreneurship in them. In the meantime, in addition to the stage of realizing entrepreneurship as a "good idea" in order to realize the potential abilities of entrepreneurs, the necessary training should be provided, so that students have the necessary knowledge and skills to establish activities in the form of entrepreneurship in a systematic way (Arefi et al, 2010). Based on this, entrepreneurship education with the aim of increasing entrepreneurial activities in schools to students should be done within the framework of the unique cultural and social context of each region (Lee & Peterson, 2000). Therefore, the current research, understanding the importance of this issue and the existence of a clear research gap in this field, has tried to answer the question: "what are the elements and characteristics of the ideal model of professional development of technical and professional art students in order to teach entrepreneurship in conservatories?" Theoretical Framework Professional development Professional development includes any activity designed to improve knowledge, skills, and attitudes. In other words, the professional development of teachers is composed of natural learning experiences, and conscious and designed direct and indirect activities, which are useful for each and every student, special groups, and even the whole school; and finally the conducted activities lead to the improvement of educational quality (Kalantari Khandani & Farrokhi, 2016).